THE IMPACT OF AUTHORITATIVE PARENTING AND SELF-CONCEPT ON RELIGIOSITY AT MUHAMMADIYAH JUNIOR HIGH SCHOOL 02 - Masitah, Widya (Proceeding International Seminar of Islamic Studies, 2024)
Study This done at school intermediate First Muhammadiyah 02. Objectives from study This For see three matter . First, look influence draft self to religiosity teenager. Second is For see influence pattern foster democratic to religiosity teenager Third is For see in a way together influence draft self And pattern foster democratic to religiosity. Sample in study This as many as 106 students. This research is quantitative research using linear regression analysis techniques multiple. Results obtained in study This namely: first, there is influence draft self to religiosity teenager. This matter can proven from magnitude mark significance 0.000 alpha 0.05 or with a calculated t value of 4.893 t table 1.659. Donations made  amounting to 18.7 %. Second, there is influence pattern foster democratic to religiosity teenager This can proven from magnitude mark significance 0.000 alpha 0.05 or with a calculated t value of 4.752 t table 1.659. Donations made amounting to 17.8 %.Third, there is influence draft self And pattern foster democratic to religiosity teenager This can proven from magnitude mark significance 0.000 alpha 0.05 or with a calculated F value of 13,424 t table 3.08. Donations made of 20.7 %